Modelo de aula virtual para mejorar el aprendizaje significativo en la Unidad Educativa Isla de Bejucal, Baba 2021 - Mayea Macías, Marlon Mauricio (2021)
The following research project consists of diagnosing the current state of meaningful learning and the implementation of a virtual classroom to improve this learning in students, through the use of a virtual classroom model, as a didactic tool in the teaching-learning process of the students, which will be used by the teachers of the Isla de Bejucal Educational Unit. This research has a non-experimental design, according to the Purpose it is applied, according to the approach it is quantitative, according to the Scope it is Exploratory and Explanatory. The sample is made up of 44 teachers from the Educational Unit who represent 100% of the study population. To collect the data, the survey technique and a questionnaire of 20 questions on a Likert scale with 5 alternatives were applied by using the Google Forms tool, evaluating the following parameters: Motivating content, personalized resources, interactive classes quality, integration of concepts, adaptive knowledge and reflective learning. From the results obtained, it is concluded that 38.6% of the teachers agree and 25.0% affirm that they totally agree with the use of the Virtual Classroom because different didactic activities can be carried out, and regarding the Use of the Virtual Classroom in the improvement of significant Learning 38.6% of the teachers responded that they agree and 22.7% say they totally agree, because the students better interpret the contents in relation to traditional teaching. Therefore, it can be concluded in a general way that teachers need this tool to improve the teaching-learning process in students of the Isla de Bejucal Educational Unit.